Impact of periprocedural morphine use on mortality in STEMI patients treated with primary PCI. - Dominika Domokos (PLoS ONE, 2021)
Background Intravenous morphine (MO) decreases the effect of all oral platelet P2Y12 receptor inhibitors in vitro and observational reports suggest that its use may be associated with larger infarct size. Yet, there are limited data available about the impact of this interaction on clinical outcomes. We studied the effect of MO on mortality in ST-segment elevation myocardial infarction (STEMI) patients treated with primary PCI using a prospective registry. Methods Of the 1255 patients who underwent primary PCI, 397 received MO based on physician's judgment. Clopidogrel was used as P2Y12 receptor antagonist in all cases. Median follow-up time was 7.5 years with 457 deaths. To adjust for confounding, two propensity score-based procedures were performed: 1 to 1 matching (PSM, 728 cases), and inverse probability of treatment weighting (IPTW) retaining data from all patients. Primary outcome measure was time to all-cause death, whereas predischarge left ventricular ejection fraction (LVEF) was used as secondary end point. Results An adequate balance on baseline covariates was achieved by both methods. We found no difference in survival as the HR (MO/no MO) was 0.98 (95% confidence interval [CI]: 0.76-1.26), p = 0.86 using PSM and 1.01 (95% CI: 0.84-1.23), p = 0.88 with IPTW. Likewise, distributions of LVEFs were similar using either methods: with PSM, median LVEFs were 50.0% (interquartile range [IQR]: 43.0%-55.3%) vs 50.0% (IQR: 42.0%-55.0%) in the no MO and MO groups, respectively (p = 0.76), whereas using IPTW, they were 50.0% (IQR: 42.5%-55.0%) vs 50.0% (IQR: 41.0%-55.0%), respectively (p = 0.86). Conclusions Our data suggest that morphine use may have no impact on long-term mortality and on predischarge ejection fraction in STEMI patients treated with primary PCI.